Sports as a cause of oxidative stress and hemolysis (2005)
More than three decades ago, it was established that anemia, a cause of tissue oxygenation deficiency, can be caused by exercise. However, this preliminary relationship really corresponds to an event where the plasma is diluted and for this reason the term «sports pseudoanemia» was made. New data relate exercise from moderated to exhaustive, with blood loss through gastrointestinal and urinary tracts, as well as erythrocytes rupture by mechanical, osmotic and oxidative events. Therefore, now the association between chronic exercise and impairment in erythrocytes number and form is clearer, which is evidence in favor of a true anemia in sports. In this anemia it is evident the ferropenic etiology. But recent information opens discussion about whether hemolytic etiology is a co adjuvant factor to anemia, and on the role of oxidative stress in it. This paper is an updated review for a relationship between sports and anemia, and for assessing causes of ferropenic anemia and for sports hemolysis. © 2005 Corporación Editora Médica del Valle.